Palm Fats as Animal Fat Analogues in Beef Burgers - Wan Rosli, W. I.; Babji, A.S.; Alina, A. R.; Mohd Suria, A. Y.; Foo, S. P. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2003)
Palm fat and red palm fat were used to replace beef fat in beef burgers. The vitamin E content was higher in palm fat burgers and red palm fat at 428 and 367 μg/g, respectively. Replacing beef fat with palm fat decreased cholesterol to 87 mg and 92 mg/100g (16-24%) in raw and cooked beef burgers, respectively. Red palm fat burgers had the highest carotene values, while beef fat burgers were the lowest. Substitution of animal fat with palm fat did not change the overall sensory acceptability of the beef burgers, showing the potential of palm fats as animal fat analogues.